2013
DOI: 10.5194/acp-13-11195-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the North Atlantic Oscillation on European aerosol ground levels through local processes: a seasonal model-based assessment using fixed anthropogenic emissions

Abstract: Abstract. The North Atlantic Oscillation (NAO) controls a large amount of the European climate variability with asymmetric impacts in both time and space. Here we investigate how the NAO impact on the local atmospheric processes (disregarding the NAO impact on the large intercontinental transport mechanisms) influences the levels of various aerosol species using simulated data under constant emissions, which are fixed to the 2005 levels in order to avoid anthropogenic-induced signals. In particular, we analyze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…Moulin et al (1997) analysed the role of the NAO in controlling the desert-dust transport into the Atlantic and Mediterranean and suggested that the NAO likely influences the distribution of anthropogenic aerosols. Jerez et al (2013) investigated the NAO influence on European aerosol concentrations through local atmospheric processes (e.g. precipitation, wind, cloudiness) and found that positive NAO promotes higher ground-level aerosol concentrations in southern regions of the Mediterranean during winter.…”
Section: Introductionmentioning
confidence: 99%
“…Moulin et al (1997) analysed the role of the NAO in controlling the desert-dust transport into the Atlantic and Mediterranean and suggested that the NAO likely influences the distribution of anthropogenic aerosols. Jerez et al (2013) investigated the NAO influence on European aerosol concentrations through local atmospheric processes (e.g. precipitation, wind, cloudiness) and found that positive NAO promotes higher ground-level aerosol concentrations in southern regions of the Mediterranean during winter.…”
Section: Introductionmentioning
confidence: 99%
“…In mid-latitudes~55 • N, 20-30 • E, during the period of June-September, negative NAO phases are associated with a stronger westerly wind flow, a higher precipitations level, a higher cloudiness and a lower air temperature [4,8]. A positive NAO during summer associated with a lower precipitation level, weaker winds and a higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations between high and low NAO phases produce large changes in the wind speed and direction over the Atlantic, the heat and moisture transport between the Atlantic and other continents [1]. Thus, NAO influences hemispheric-scale and continent-scale pollution transport [6][7][8]. The backward trajectories analysis in Lithuania indicates that the predominant origin of air masses is South-western Europe and North Atlantic region [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…RH, PR and TS can impact aerosol concentrations by altering aerosol thermodynamics, wet deposition and chemical reaction rates (Dawson et al 2007;Kleeman 2008;Jacob and Winner 2009). The wind fields at 850 hPa are considered here because the transport by the lower troposphere wind is important for surface-layer aerosol concentrations in the three studied regions (Zhang et al 2010;Jerez et al 2013;Gong et al 2006).…”
Section: Methodsologymentioning
confidence: 99%
“…Considering that the North Atlantic Oscillation (NAO) is the most important circulation pattern over Europe, the NAO might have contributed to the IAVs of surface aerosol concentrations in Europe. The impact of NAO on surface aerosol concentrations in Europe has been studied by Jerez et al (2013) for years of 1970−1999.…”
Section: Key Meteorological Variables That Drive the Interannual Varimentioning
confidence: 99%